As relações de trabalho na era globalizada: o desafio da ampliação da tutela aos trabalhadores. - Pessoa, Anna Stephanie de Brito Veiga (2013)
The paper focuses on the changes in the labor market towards the corporate restructuring, highlighting the emergence of a collective of workers, called parasubordinate workers or economically dependent self-employed. Therefore, a legal theoretic instrumental survey was undertaken, of qualitative nature, using dialectic and analytical methods to approach the subject. As procedure methods; historical, comparative and interpretation systems were applied, and finally indirect documentation was used as a research technique. The State restricted intervention in the economy facing the neoliberal policies enabled that companies promoted a productive restructuring, to mold to the context of international economies, dismantling the labor market structures. Precarious work was intensified in the 1990s, since it was up to the workers the choice between unemployment and working in precarious conditions, through atypical contracts. Subcontracting and outsourcing gained prominence in business decentralization, allowing companies to focus their attention only in activities related to the valorization of brands and their products, transferring to others the execution of the production process. The use of self-employed manpower without a stable relation took over society. The self-employed, with high or low qualifications are regimented to develop activities directly related to the business dynamics, consuming much of their workday, being unable, for them, to provide services to other companies. The Law, then, according to the parasubordination theory - the labor insertion tool used in Italy, and improved in Spain, through the Statute for Autonomous Work - aims to protect these workers who are legally independents but economically dependents, guaranteeing minimum rights to those who work either on their own, whether on behalf of others, giving an identity to the working class to mobilize and act searching for the achievement of its development.